2000
DOI: 10.1093/bja/85.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and respiratory effects of low-dose spinal morphine for postoperative analgesia following knee arthroplasty

Abstract: A randomized, double-blind study of 38 patients undergoing total knee replacement was undertaken to compare the efficacy and respiratory effects of low-dose spinal morphine and patient-controlled i.v. morphine against patient-controlled i.v. morphine alone. Patients received either morphine 0.3 mg or saline 0.3 ml with 0.5% heavy spinal bupivacaine 2-2.5 ml. Respiratory effects were measured continuously for 14 h postoperatively with an Edentec 3711 respiratory monitor. There was an improvement in pain relief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 22 publications
3
69
0
1
Order By: Relevance
“…Unfortunately, narcotic analgesia is associated with unwanted side effects such as PONV. Many other factors contribute to PONV, including polymethylmethacrylate use, blood loss, and surgical pain [3,7,9,20,26,28]. PONV can occur during the entire hospitalization and can be severe and disabling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, narcotic analgesia is associated with unwanted side effects such as PONV. Many other factors contribute to PONV, including polymethylmethacrylate use, blood loss, and surgical pain [3,7,9,20,26,28]. PONV can occur during the entire hospitalization and can be severe and disabling.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetic agents and narcotic analgesia commonly cause severe postoperative nausea and vomiting (PONV) after total joint arthroplasty (TJA) [3,7,9,20,26,28]. PONV after lower extremity TJA has a reported incidence of 20 to 83% [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Intrathecal morphine provides an excellent long-lasting analgesia and the addition of morphine to spinal anesthesia has been used for postoperative analgesia after many surgical procedures. [3][4][5][6][7][8][9][10] Cunningham et al demonstrated that intrathecal morphine was effective for analgesia after TURP. 11 On the other hand, intrathecal morphine is often accompanied by adverse effects such as pruritus, nausea and respiratory depression.…”
Section: Méthode : L'étude Prospective Et à Double Insu Comportait 42mentioning
confidence: 99%
“…Lower doses of ITM have been used effectively for analgesia following Cesarean section (100 µg), 6 hip replacement surgery (100 µg) 7 and knee replacement surgery (300 µg). 8 There are reports of the use of lower doses of ITM (250 µg or 500 µg) as part of a fast-track approach in cardiac surgery, with no effect on extubation time (six to seven hours). 9 The current study was designed as a retrospective, comparative, continuous quality improvement audit.…”
mentioning
confidence: 99%
“…Alhashemi et al 9 concluded that 250 µg was the optimal dose to reduce postoperative morphine requirements without delaying extubation, while Chaney et al 5 used 10 µg·kg -1 of ITM without benefit. Dose finding studies in gynecology 20 and orthopedics 8 suggest 300 µg of ITM to be efficacious and safe, while Palmer 6 showed 100 µg to be effective for analgesia after Cesarean section. Whether even lower doses of ITM in cardiac surgery would remain effective while reducing side effects is unclear.…”
mentioning
confidence: 99%